Immunohistochemical evaluation of tissues following bone implant extraction from upper and lower limb - Bielniková-Kryštofová, Hana; Oldřich, Motyka; Židlík, Vladimír; Žiak, Dušan; Szotkovská, Iveta; Škarda, Jozef; Voves, Jiří; Pometlová, Jana; Pleva, Leopold; Havlíček, Miroslav; Čabanová, Kristina (Histology and histopathology, 2023)
Fractured bones can regenerate and restore their biological and mechanical properties to the state prior to the damage. In some cases, however, the treatment of fractures requires the use of supportive implants. For bone healing, three processes are essential: the inflammatory phase, the repair phase and the remodelling phase. A proper course of the first - inflammatory - stage is important to ensure a successful fracture healing process. In our study, we evaluated tissue samples immunohistochemically from the area surrounding the fractures of upper and lower limbs (bone tissue, soft tissue, and the implant-adhering tissue) for markers: CD11b, CD15, CD34, CD44, CD68, Cathepsin K, and TRAcP that are linked to the aforementioned phases. In soft tissue, higher expressions of CD68, CD34, CD15 and CD11b markers were observed than in other locations. TRAcP and Cathepsin K markers were more expressed in the bone tissue, while pigmentation, necrosis and calcification were more observed in the implant-adhering tissue. Since even the implant materials commonly perceived as inert elicit the observed inflammatory responses, new surface treatments and materials need to be developed.
Keywords: kyselá fosfatasa rezistentní k tartarátu; Fracture Healing; Tartrate-Resistant Acid Phosphatase; kosti a kostní tkáň; Cathepsin K; kathepsin K; Bone and Bones; hojení fraktur; dolní končetina; Lower Extremity